2016
DOI: 10.1021/acscatal.6b00961
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Glycerol to Dicarboxylic Acids Using Cobalt Catalysts

Abstract: In this paper, the performance of cobalt-based catalysts was reported for oxidation of glycerol to dicarboxylic acids such as tartronic and oxalic acids. Cobalt catalysts supported on Mg3Al­(OH) y(CO3) z structures prepared by a two-step modified sol–gel method showed 100% glycerol conversion with 64% and 24% selectivity toward tartronic and oxalic acids under mild conditions (55–70 °C and 0.1 MPa O2). Surface and bulk characterization by N2 adsorption/desorption, X-ray diffraction, and temperature-programmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 30 publications
(60 reference statements)
2
50
0
Order By: Relevance
“…Little is known on glycerol oxidation in the presence of non‐noble metal catalysts . In another work, we reported lattice incorporated Co catalysts prepared by conventional co‐precipitation and modified sol‐gel methods . Co species can be atomically incorporated into hydrotalcite network during co‐precipitation, while in modified sol‐gel method, Co hydroxide species are immobilized on the surface of layered double hydroxide surface (Figure ).…”
Section: Figurementioning
confidence: 99%
“…Little is known on glycerol oxidation in the presence of non‐noble metal catalysts . In another work, we reported lattice incorporated Co catalysts prepared by conventional co‐precipitation and modified sol‐gel methods . Co species can be atomically incorporated into hydrotalcite network during co‐precipitation, while in modified sol‐gel method, Co hydroxide species are immobilized on the surface of layered double hydroxide surface (Figure ).…”
Section: Figurementioning
confidence: 99%
“…The plot of the selectivity over the reaction time (Fig. 5) shows that the selectivity towards the C 3 products glyceric acid and tartronic acid increases within the first 1 to 1.5 h. At longer reaction times, increasing C-C cleavage into the C 2 and C 1 products oxalic acid, glycolic acid, and formic acid sets in, as it is also observed in the use of other non-noble 42,49 and noble 73 metal catalysts.…”
Section: View Article Onlinementioning
confidence: 55%
“…An attractive alternative to noble metals in selective oxidation reactions is copper, which was demonstrated to be active for the selective oxidation of various alcohols and polyols. [37][38][39][40][41] However, there are only few reports on selective oxidation of glycerol in basic media with non-noble metal catalysts, such as with the toxic and carcinogenic cobalt, [42][43][44] layered double hydroxide supported transition metals, [45][46][47] or using hydrogen peroxide instead of molecular oxygen as an oxidizing agent. 48,49 Key factors for the fabrication of efficient supported catalysts are firstly a high dispersion of the active component on the support material; secondly, high surface areas of the support; and thirdly, large porosity to allow efficient diffusion of reactants to the active centers.…”
Section: Introductionmentioning
confidence: 99%
“…60 % and 30 % for glyceric and tartronic acids, respectively 68) . Recently, Jin et al reported Co/Mg _ Al catalyst prepared by sol-gel method was found to be active for aqueous glycerol oxidation at 343 K with 0.1 MPa O2 and NaOH, forming tartronic acid with 64 % selectivity at 100 % glycerol conversion 69) . The Co species concentrated on the Mg3AlOx surface were proposed to catalyze this deep glycerol oxidation.…”
Section: Oxidative Transformations Of Glycerolmentioning
confidence: 99%